High-Intensity Red Light-Emitting Diode Irradiation Suppresses the Inflammatory Response of Human Periodontal Ligament Stem Cells by Promoting Intracellular ATP Synthesis - Nobuhiro Yamauchi; Emika Minagawa; Kazutaka Imai; Kenjiro Kobuchi; Runbo Li; Yoichiro Taguchi; Makoto Umeda (Life, 2022)
Periodontitis is an inflammatory lesion in the periodontal tissue. The behavior of human periodontal ligament stem cells (hPDLSCs), which play an important role in periodontal tissue regeneration, is restricted by the influence of inflammatory mediators. Photobiomodulation therapy exerts anti-inflammatory effects. The purpose of this study was to investigate the effects of light-emitting diode (LED) irradiation on the inflammatory responses of hPDLSCs. The light source was a red LED (peak wavelength: 650 nm), and the total absolute irradiance was 400 mW/cm2. The inflammatory response in hPDLSCs is induced by tumor necrosis factor (TNF)-α. Adenosine triphosphate (ATP) levels and pro-inflammatory cytokine (interleukin [IL]-6 and IL-8) production were measured 24 h after LED irradiation, and the effects of potassium cyanide (KCN) were investigated. LED irradiation at 6 J/cm2 significantly increased the ATP levels and reduced TNF-α-induced IL-6 and IL-8 production. Furthermore, the inhibitory effect of LED irradiation on the production of pro-inflammatory cytokines was inhibited by KCN treatment. The results of this study showed that high-intensity red LED irradiation suppressed the TNF-α-stimulated pro-inflammatory cytokine production in hPDLSCs by promoting ATP synthesis. These results suggest that high-intensity red LED is a useful tool for periodontal tissue regeneration in chronically inflamed tissues.